Ethanol metabolism in the generation of new antigenic determinants on liver cells. Issue 2 (February 1986) - Crossley, I R; Neuberger, J; Davis, M; Williams, R; Eddleston, A L
Abstract : Antibodies directed against ethanol altered liver cell components have been detected in the serum of nearly 50% of patients with alcoholic liver disease although the pathogenetic mechanisms are unclear. The importance of ethanol metabolism in the generation of new antigenic determinants on liver cells was investigated by in vivo inhibition of alcohol or acetaldehyde dehydrogenase and an induced cytotoxicity assay. There was a significant reduction in cytotoxicity to hepatocytes isolated from rabbits treated with ethanol 1 g/kg when the metabolism of ethanol to acetaldehyde by alcohol dehydrogenase was inhibited. In contrast when the oxidation of acetaldehyde was inhibited by disulfiram cytotoxicity was significantly enhanced. These results show that ethanol metabolism is integral to the expression of the ethanol related determinant and suggest that an impaired ability to metabolism acetaldehyde could lead to the development of immunological reactions to alcohol altered liver membrane antigens.